The Specific Judo Training Program Combined With the Whole Body Cryostimulation Induced an Increase of Serum Concentrations of Growth Factors and Changes in Amino Acid Profile in Professional Judokas - Jaworska, Joanna; Laskowski, Radoslaw; Ziemann, Ewa; Zuczek, Klaudia; Lombardi, Giovanni; Antosiewicz, Jedrzej; Zurek, Piotr (Frontiers in Physiology, 2021)
This study aimed to evaluate the effect of a specific training program, supported by 10 sessions of whole body cryostimulation, on growth factors concentrations, amino acids profile and motor abilities in professional judokas. Ultimately, twelve athletes took part in the study. They were randomly assigned to the cryostimulation group (CRY, n = 6) or the control group (CON, n = 6). During 2 weeks of the judo training program, the CRY group performed 10 cryo-sessions (3-min, at a temperature of −110°C) and the CON group rested passively. Anthropometric measurements, a strength test, the Special Judo Efficiency Test (SJET) were assessed 2 days before and after the judo training program. Blood samples were collected at rest, 1 h after the first and the second SJET and 1 h after the first and the last cryo-session to establish growth factors and amino acid concentrations. Lactate level was measured before, immediately after and 1 h after the first and the second SJET. The applied intervention resulted in a significant increase of resting concentrations of brain-derived neurotrophic factor (from 10.23 ± 1.61 to 15.13 ± 2.93 ng⋅ml–1; p = 0.01) and insulin-like growth factor 1 (IGF-1; from 174.29 ± 49.34 to 300.50 ± 43.80 pg⋅ml–1; p = 0.00) in the CRY group. A different response was registered 1 h directly post SJET in the CRY group (a significant increase of IGF-1, interleukin 15 and irisin: p = 0.01; p = 0.00; p = 0.03). Additionally, the significant drop of proline and leucine concentrations in the CRY group was obtained. Athletes’ performance remained unchanged in both groups. However, subjects perceived positive changes induced by the intervention – not directly after cryostimulation but in response to the specific training workload. The increase of growth factors concentrations and the improvement of amino acid profile (proline and leucine) contributed to maintaining a high level of muscle function.